Polycarbonate sunlight plate and preparation method thereof
By introducing phosphorus and nitrogen elements into the polycarbonate sun panel, combined with modified MBS resin and composite antioxidants, the problems of poor thermal stability and yellowing of the polycarbonate sun panel are solved, and good flame retardant of the material is achieved , high temperature resistance and oxidation resistance, improve its comprehensive performance and service life.
Patent Information
- Application Number
- CN202510056149.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polycarbonate sun panels have poor thermal stability in high temperature and high shear processing states, which can easily cause yellowing of transparent products and are susceptible to ultraviolet radiation in outdoor use, limiting their application in larger products.
By introducing phosphorus and nitrogen into polycarbonate, combined with modified MBS resin and composite antioxidants, the flame retardant, high temperature resistance and oxidation resistance of the material are improved. Specific methods include introducing phenyl phosphate and boron nitride, modifying the MBS resin using acrylic silsesquisilane, and synthesizing a composite antioxidant containing boron nitride grafted fluoro-containing silane and antioxidant.
It achieves good flame retardant effect of polycarbonate sun panels, improves its stability and weather resistance at high temperatures, enhances the light transmittance and mechanical properties of the material, and extends its service life.
Smart Images

Figure CN119463450A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polycarbonate sunlight panels, in particular to a polycarbonate sunlight panel and a preparation method thereof. Background Art
[0002] Polycarbonate (PC) is an important thermoplastic engineering plastic developed in the late 1950s. It has excellent and balanced mechanical, heat resistance and electrical properties, and has a transmittance comparable to that of glass, but has higher impact strength than glass. It is widely used in the production of various polycarbonate panels and endurance panels. The polycarbonate panels made can be used to make carports, balcony awnings, greenhouse lighting carports, etc.
[0003] The processing performance of polycarbonate materials is poor. Under high temperature and high shear processing conditions, polycarbonate has poor thermal stability, and the ester bonds contained are very easy to break. The degradation caused by this will cause yellowing and other undesirable phenomena in transparent products, causing the transparent products to appear yellow. In addition, in outdoor use environments, long-term ultraviolet irradiation is also easy to cause yellowing of polycarbonate materials, thus greatly limiting its application in large-volume products. Patent CN102719074B discloses a transparent non-yellowing polycarbonate composition and a preparation method. The composition is prepared using polycarbonate, deionized water and an antioxidant as raw materials, and the aspect ratio, screw temperature and screw speed of a twin-screw extruder are controlled at the same time. The transparent non-yellowing polycarbonate composition has high light transmittance, yellowing resistance and low yellowness value, but the composition prepared by directly blending the antioxidant has poor stability, and the antioxidant is easy to precipitate during long-term use, thereby reducing the stability of the material and the mechanical properties of the material are poor.
[0004] Patent CN111873585B discloses an anti-aging PC sun panel and its preparation method. Polycarbonate, organic montmorillonite, hydrophobic agent and antioxidant are used as the main material layer raw materials of the anti-aging PC sun panel. The obtained PC sun panel has strong tensile strength and maximum penetration of drop hammer impact. However, the invention uses the anti-ultraviolet layer as the upper and lower surfaces of the main material layer. The anti-ultraviolet layer is easily scratched when exposed to the outer layer for a long time, thereby reducing its anti-ultraviolet effect. In addition, the material is exposed to the outdoors for a long time, and after long-term rain and high temperature scouring, the overall performance of the material will also be reduced. Although the polycarbonate material has a certain hydrophobicity, the hydrophobicity is not high.
[0005] Patent CN115895009B discloses a wear-resistant, super-hydrophobic polycarbonate substrate and a preparation method. The patent uses glycidyl methacrylate to graft-modify polytetrafluoroethylene micropowder, uses perfluoroalkyl mercaptan to surface-modify nano-molybdenum disulfide powder, disperses the modified mixture in methanol, and deposits the substance on the surface of the polycarbonate material by spray deposition technology. The material has good hydrophobicity and wear resistance, but the preparation cost is relatively high.
[0006] Patent CN114103358B discloses a flame retardant reinforced polycarbonate composite board and its preparation method. By modifying organic particles such as rigid styrene-butadiene-methacrylate copolymer and introducing a styrene-siloxane polymer with a hyperbranched molecular structure on its surface, the obtained composite board has good flame retardant effect. However, since it needs to be hot pressed with carbon fiber non-woven fabric, the light transmittance of the material is not high.
[0007] Patent CN102276821A discloses a polycarbonate copolymer and a method for manufacturing the same. The polycarbonate copolymer of the invention contains structural units of dihydroxy compounds and structural units derived from alicyclic dihydroxy compounds. The polycarbonate prepared by the invention has excellent transparency.
[0008] Although certain progress has been made in the research of polycarbonate materials, in the prior art, polycarbonate materials still have problems such as poor hydrophobicity, poor mechanical properties, low hydrophobicity, low light transmittance and poor flame retardancy.
[0009] Therefore, a polycarbonate sunlight board and a preparation method thereof are proposed. Summary of the invention
[0010] The purpose of the present invention is to provide a polycarbonate sun panel and a preparation method thereof. By introducing phosphorus and nitrogen into polycarbonate, the sun panel has good flame retardant effect; by introducing fluorine-containing silane into the surface of a composite antioxidant and using acrylsilsesquiane to modify MBS resin, the prepared sun panel has good high temperature resistance and increased water contact angle; by synthesizing a composite antioxidant containing boron nitride grafted fluorine-containing silane and an antioxidant for use in the sun panel, the composite antioxidant is not easy to precipitate, and the sun panel has good weather resistance; by adjusting the amount of acrylsilsesquiane in the modified MBS resin, changing the type of antioxidant one in the composite antioxidant and the ratio to antioxidant two, the sun panel has good tensile properties and impact resistance; by reasonably controlling the amount of the modified MBS resin and the composite antioxidant, changing the temperature of each zone of melt extrusion of a twin-screw extruder, the sun panel has high light transmittance and good comprehensive performance.
[0011] To achieve the above object, the present invention provides the following technical solutions: A polycarbonate sunlight board, comprising the following components: Polycarbonate resin, 0-58 parts of modified MBS resin and 0-20 parts of composite antioxidant; The modified MBS resin preparation method is as follows: adding methacrylic acid aqueous solution and potassium persulfate to molten MBS resin, adding dopamine aqueous solution and 1-2 parts of 1,3-dicyclohexylcarbodiimide after reaction, stirring and reacting for 3 hours to obtain a dopamine grafted modified MBS resin precursor; the amount of dopamine in the dopamine aqueous solution is 8-12 parts; continuing to add 0-23.5 parts of phenyl phosphate, stirring and reacting for 10 hours, adding the 1,3-dicyclohexylcarbodiimide and 0-47 parts of acrylsilsesquiane, and reacting to obtain the modified MBS resin; The preparation method of the composite antioxidant is as follows: heating a boron nitride dispersion to 60°C, and dripping a fluorine-containing silane solution thereinto under stirring to obtain a reaction solution; the ratio of boron nitride to fluorine-containing silane in the reaction solution is 1:0-0.4; adding deionized water to the reaction solution and reacting for 5 hours, washing and drying to obtain boron nitride grafted fluorine-containing silane; using potassium hydroxide solution to adjust the pH of the antioxidant solution to 8.0-9.5, and reflux reaction at 60°C for 10 hours to obtain an antioxidant hydrolyzate; the antioxidant comprises an antioxidant 1 and an antioxidant 2 in a ratio of 1-4:1; mixing 27-30 parts of the boron nitride grafted fluorine-containing silane and 16-21 parts of the antioxidant hydrolyzate to obtain a mixture; adding a mixed solution of ethanol and toluene and concentrated sulfuric acid to the mixture, stirring, ultrasonicating, reflux reaction at 110°C for 9 hours to end, cooling, layering, washing and drying to obtain the composite antioxidant.
[0012] Preferably, the modified MBS resin is 52-58 parts; the composite antioxidant is 8-20 parts.
[0013] Preferably, the phenyl phosphate is one of diphenyl phosphate and phenyl phosphate benzenesulfonic acid.
[0014] Preferably, the amount of phenyl phosphate is 18-23.5 parts.
[0015] MBS resin is modified, the unsaturated bond of methacrylic acid copolymerizes with the methacrylic acid ester in the MBS resin, and then the amino group in the dopamine molecule condenses with the carboxyl group of methacrylic acid under the action of the catalyst 1,3-dicyclohexylcarbodiimide. The amount of the catalyst is reasonably adjusted to enhance the connection between the components. Then diphenyl phosphate or phenyl phosphate benzenesulfonic acid is introduced, the hydroxyl group of diphenyl phosphate is connected with the hydroxyl group of dopamine through hydrogen bonding, and phenyl phosphate benzenesulfonic acid reacts with the hydroxyl group of dopamine and connects through ether bonds. The phosphorus element of phenyl phosphate and the nitrogen element of dopamine work synergistically, and have a good flame retardant effect. In addition, boron nitride, on the one hand, acts as a carrier of the antioxidant, and on the other hand, it also improves the flame retardant properties of the material.
[0016] Preferably, the amount of the acrylsilsesquiane is 40-47 parts.
[0017] Under the action of the catalyst, acryl silsesquiane polymerizes with the double bond structure in the MBS resin, thereby introducing acryl silsesquiane into the resin and finally blending it with the polycarbonate material. The cage structure of acryl silsesquiane strengthens the cross-linking degree between polycarbonate molecules and prevents the degradation and breakage of polycarbonate molecules. In addition, the introduction of cage silane enhances the water resistance of the material and improves the overall heat resistance of the material.
[0018] Preferably, the fluorine-containing silane is one of nonafluorotriethoxysilane, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, heptadecafluorooctyltriethoxysilane, heptadecafluorooctyltripropoxysilane, pentafluorooctyltripropoxysilane and heptadecafluorooctyltripropoxysilane.
[0019] Preferably, the ratio of the boron nitride to the fluorine-containing silane is 1:0.3-0.4.
[0020] Fluorosilane hydrolyzes under acidic conditions, breaking the silicon-oxygen bond, and the broken fluorine-containing silane reacts with the hydroxyl group on the surface of boron nitride, thereby introducing the fluorine-containing silane to the surface of boron nitride, improving the dispersion stability of boron nitride in the system and avoiding the accumulation of boron nitride in the system. The fluorine atoms of the fluorine-containing silane are arranged alternately in the system, improving the hydrophobicity and high temperature resistance of the material.
[0021] Preferably, the oxidant 1 is one of antioxidant 1010, antioxidant 1035, antioxidant 245, antioxidant 259 and antioxidant 3114.
[0022] Preferably, the second antioxidant is antioxidant TH-412S.
[0023] Antioxidant 1010, Antioxidant 1035, Antioxidant 245, Antioxidant 259 are hindered phenol antioxidants. Under high temperature and alkaline conditions, phenol antioxidants are hydrolyzed into multi-molecule antioxidants containing carboxyl groups. Boron nitride is surface-modified to obtain boron nitride grafted fluorinated silane. The unreacted hydroxyl groups on the surface of boron nitride are esterified with the carboxyl groups contained in the hydrolyzate to obtain a composite antioxidant containing boron nitride grafted fluorinated silane and antioxidants. Antioxidant 3114 is a hindered amine and hindered phenol antioxidant. After hydrolysis, an antioxidant product containing amine is formed, which is then grafted with boron nitride.
[0024] The active hydroxyl groups in the antioxidant can capture free radicals and terminate the active chain reaction, preventing the oxidation process from proceeding, thereby improving the yellowing of polycarbonate sunlight sheets. The components are firmly connected, and the composite antioxidant is entangled and interpenetrated with the modified MBS resin and polycarbonate resin, which can effectively block the precipitation of the active ingredients of the antioxidant from the material, thereby ensuring the antioxidant effect.
[0025] A method for preparing a polycarbonate sun panel, wherein the polycarbonate sun panel is prepared by mixing a polycarbonate resin, a modified MBS resin and a composite antioxidant, and then putting the mixed material into a twin-screw extruder, controlling the temperature of the conveying zone to be 180-230°C, and the temperature of other zones to be 250-310°C, and then melt-extruding, drying and sheeting. The polycarbonate sun panel comprises the polycarbonate resin, the modified MBS resin and the composite antioxidant. The polycarbonate sun panel has an oxygen index of 29.3-41.9 and a flame retardant grade of V-0, V-1 and V-2. The polycarbonate sun panel has a hydrophobic angle of 97.7°-146.1°, and a Vicat softening temperature of 70.9-116.2°C; a color difference of 0.9-3.9, a yellowness index change of 0.7-2.5, and a drop hammer impact (perforation characteristic) performance retention rate of 80%-90%; a maximum drop hammer impact penetration force of 642-752N, and a tensile strength of 67.3-88.4MPa; a light transmittance of 70%-92%, and a yellowing index change of 0.6-2.6.
[0026] Compared with the prior art, the present invention has the following beneficial effects: 1. By introducing phenyl phosphate and boron nitride, the system is connected through chemical bonds, which improves its compatibility with the components. By introducing phosphorus, a dense coating layer is formed on the surface of the material when a fire occurs, preventing the occurrence of fire. The introduced nitrogen element reduces the concentration of flammable gas, achieving a good flame retardant effect.
[0027] 2. The present invention introduces fluorine-containing silane into the reaction system and uses acryl silsesquiane to modify the MBS resin, thereby improving the compatibility of each component by chemical bond connection and ensuring the stability of each component blended with the polycarbonate resin. The introduction of different types of silane improves the water resistance and high temperature resistance of the polycarbonate sun panel and prolongs the life of the sun panel under outdoor use conditions.
[0028] 3. A composite antioxidant containing boron nitride grafted fluorinated silane and an antioxidant is synthesized and used to prepare polycarbonate sunlight panels. The antioxidant is not easy to precipitate from the material, and the compatibility between the material components is good. After being used in the natural environment for 2000 hours, the sunlight panel still has good oxidation resistance and good weather resistance.
[0029] 4. By adjusting the amount of acryl silsesquiane in the modified MBS resin, changing the type of antioxidant 1 in the composite antioxidant and the ratio to antioxidant 2, the unreacted unsaturated double bonds in the modified MBS resin are fully utilized, and the flexibility of the polycarbonate sun sheet is improved in synergy with acryl silsesquiane and the composite antioxidant. The rigid structure in the modified MBS resin and the composite antioxidant also promotes the improvement of the impact resistance of the polycarbonate material. The mechanical properties of the sun sheet are good.
[0030] 5. The present invention reasonably controls the dosage of the modified MBS resin and the composite antioxidant, and also controls the temperature of the conveying zone of the twin-screw extruder and the average temperature of other zones. The obtained polycarbonate sun sheet has high light transmittance, which meets the daily use requirements of the material, and has good yellowing resistance and good comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The yellowing resistance test results of polycarbonate sunlight panels prepared in Examples 30-38 of the present invention and Comparative Example 4 are shown. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] See also Figure 1 The present invention provides a polycarbonate sunlight board and a preparation method thereof, and the technical scheme is as follows: MBS resin CAS 25053-09-2; diphenyl phosphate CAS: 838-85-7; phenyl phosphate benzenesulfonic acid CAS: 63174-10-7; antioxidant 1010 CAS: 6683-19-8; antioxidant 1035 CAS: 41484-35-9; antioxidant 245 CAS: 36443-68-2; antioxidant 259 CAS: 35074-77-2; antioxidant 3114 CAS: 27676-62-6; antioxidant TH-412S CAS: 29598-76-3; 1,3-dicyclohexylcarbodiimide CAS: 538-75-0; Nonafluorotriethoxysilane CAS: 102390-98-7; Tridecafluorooctyltrimethoxysilane CAS: 85857-16-5; Tridecafluorooctyltriethoxysilane CAS: 51851-37-7; Heptadecafluorooctyltriethoxysilane CAS: 101947-16-4; Heptadecafluorooctyltripropoxysilane CAS: 521084-64-0; Pentafluorooctyltripropoxysilane CAS: 885275-56-9; Heptadecafluorooctyltripropoxysilane CAS: 853403-04-0.
[0034] Unless otherwise specified, other substances are substances used in conventional chemical experiments. All reagents used in the present invention are of analytical grade.
[0035] Example 1 125 parts of polycarbonate resin, 52 parts of modified MBS resin and 8 parts of composite antioxidant are uniformly mixed to obtain a mixture; The mixed material is put into a twin-screw extruder, the temperature of the conveying zone is controlled to be 190°C, the temperature of other zones is controlled to be 250°C, and the screw speed is controlled to be 650rpm; after melt extrusion, it is dried to obtain a mixed masterbatch; the mixed masterbatch is put into an injection molding machine to produce a sheet to obtain a polycarbonate sun sheet.
[0036] The preparation method of modified MBS resin is as follows: 110 parts of MBS resin are added into a reactor, the temperature is raised to 160°C, and the mixture is stirred to obtain a molten MBS resin; a 10% by mass aqueous solution of methacrylic acid is added into the molten MBS resin, and 5 parts of potassium persulfate are added, and the mixture is stirred for reaction for 8 hours to obtain a modified MBS resin precursor; the amount of methacrylic acid is 6 parts; a 20% by mass aqueous solution of dopamine is added into the modified MBS resin precursor, and 2 parts of 1,3-dicyclohexylcarbodiimide are added, and the mixture is stirred for reaction for 3 hours to obtain a dopamine grafted modified MBS resin precursor; the amount of dopamine is 12 parts; 18 parts of phenyl phosphate are continuously added, and the mixture is stirred for reaction for 10 hours to obtain a modified MBS resin intermediate; phenyl phosphate is diphenyl phosphate; 3 parts of 1,3-dicyclohexylcarbodiimide and 45 parts of acrylsilsesquiane are added into the modified MBS resin intermediate to obtain a modified MBS resin.
[0037] The preparation method of the composite antioxidant is as follows: The boron nitride powder is dispersed in anhydrous ethanol, and glacial acetic acid is added dropwise to adjust the pH value to 4 to obtain a boron nitride dispersion; the volume ratio of the boron nitride powder to anhydrous ethanol is 1:200; the fluorine-containing silane is dissolved in ethanol to obtain a fluorine-containing silane solution; the volume ratio of the fluorine-containing silane to ethanol is 0.5:1; the boron nitride dispersion is heated to 60°C, and the fluorine-containing silane solution is added dropwise thereto under stirring to obtain a reaction solution; the volume ratio of boron nitride to fluorine-containing silane in the reaction solution is 1:0.4; deionized water is added to the reaction solution, reacted for 5 hours, and the solution is repeatedly washed with anhydrous ethanol and water, and dried to obtain boron nitride grafted with fluorine-containing silane; The antioxidant is dissolved in acetone to obtain an antioxidant solution; the volume ratio of the antioxidant to acetone is 1:150; the pH of the antioxidant solution is adjusted to 8.5 using a mixture of potassium hydroxide and methanol water, the temperature is raised to 60°C, refluxed for 10 hours, the solvent is recovered, and the antioxidant hydrolyzate is obtained by washing and drying; the amount of potassium hydroxide used is 3% of the antioxidant; the fraction ratio of potassium hydroxide to methanol and water in the mixture of potassium hydroxide and methanol water is 2:3:7; the antioxidant includes antioxidant one and antioxidant two; the fraction ratio of antioxidant one to antioxidant two is 4:1; antioxidant two is antioxidant TH-412S.
[0038] 30 parts of boron nitride grafted fluorinated silane and 20 parts of antioxidant hydrolyzate are mixed to obtain a mixture; 500 parts of a mixed solution of ethanol and toluene and 1.5 parts of concentrated sulfuric acid are added to the mixture, and the mixture is stirred and ultrasonicated for 30 minutes to obtain a composite antioxidant precursor; the composite antioxidant precursor is heated to 110° C., refluxed for 9 hours, cooled to room temperature, layered, washed and dried to obtain a composite antioxidant.
[0039] Embodiment 2-14 Different from Example 1, the following preparation conditions are changed, as shown in Table 1.
[0040] Comparative Example 1 Different from Example 1, no phenyl phosphate was added.
[0041] Embodiment 15 The polycarbonate sun panels prepared in Examples 1-14 and Comparative Example 1 were subjected to flame retardant performance tests. The flame retardant performance was tested with reference to GB / T2406-93 "Plastic Combustion Performance Test Method Oxygen Index Method", and the oxygen index was measured using an intelligent critical digital display oxygen index analyzer, and the flame retardant performance was tested. The sample size was 120 mm × 6 mm. The final test results are shown in Table 2.
[0042]
[0043] The polycarbonate sunlight sheet prepared by the present invention has an oxygen index of 29.3-41.9, and a flame retardant grade of V-0, V-1 and V-2. In Examples 1-4, by changing the amount of the catalyst 1,3-dicyclohexylcarbodiimide, the flame retardant effect changes. When the amount of Example 2 is 1.8 parts, the oxygen index is the highest. At this time, the effect of dopamine and MBS resin being chemically bonded is the best. Dopamine is then covalently bonded to phenyl phosphate, and the flame retardant effect is the best. The results of Example 5 and Example 2 show that by changing the type of phenyl phosphate, as shown in Example 5, the oxygen index is improved. The results of Examples 5-9 show that by reasonably adjusting the amount of dopamine and phenyl phosphate, the oxygen index shows an overall trend of increasing, decreasing and increasing. The flame retardant effect of Example 8 is the worst, and the flame retardant grade is only V-1. Examples 10-12 increase the amount of phenyl phosphate, and the oxygen index of Example 11 reaches the highest, which is 41.9. The results of Examples 11, 13 and 14 show that the oxygen index gradually decreases as the amount of fluorinated silane grafted with boron nitride is reduced. Comparative Example 1 does not add phenyl phosphate, and the flame retardant grade is only V-2.
[0044] Examples 16-28 Different from Example 1, the type and amount of silane are changed, as shown in Table 3.
[0045] Comparative Example 2 Different from Example 1, no acrylsilsesquiane was added.
[0046] Comparative Example 3 Different from Example 1, no fluorine-containing silane is added.
[0047] Embodiment 29 The polycarbonate sun panels prepared in Examples 16-28 and Comparative Examples 2 and 3 were subjected to performance tests. The water contact angle was tested using a Theta Flex water drop angle measuring instrument to examine the hydrophobic properties of the sun panels. The Vicat softening temperature of the sun panels was tested using a RBWK-300A Vicat temperature tester, specifically referring to ISO 306:2013 for the determination of the Vicat softening temperature of plastic thermoplastic materials, with a test load of 50N and a speed of 120°C / hr. The final test results are shown in Table 3.
[0048]
[0049] The polycarbonate sun sheet prepared by the present invention has a hydrophobic angle of 97.7°-146.1° and a Vicat softening temperature of 70.9-116.2°C. The results of Examples 16-20 show that when the type of fluorine-containing silane remains unchanged, as the amount of acrylsilsesquisilane decreases, the hydrophobic angle gradually decreases, and the Vicat softening temperature shows an overall decreasing trend. The results of Examples 21-26 show that with the increase of the molecular chain of the fluorine-containing silane and the increase of the amount of fluorine atoms introduced, the hydrophobic angle of the material gradually increases, and the Vicat softening temperature also increases accordingly. As shown in Examples 21-24, when the amount of fluorine atoms is constant, as the length of the silicon oxygen side chain in the fluorine-containing silane increases, the hydrophobic angle does not change significantly, and the Vicat softening temperature increases accordingly. The results of Examples 26-28 show that by reducing the amount of fluorine-containing silane in boron nitride and fluorine-containing silane, the hydrophobic angle and Vicat softening temperature decrease. In Comparative Examples 2 and 3, when no acrylsilsesquiane or fluorine-containing silane was added, respectively, the water resistance and heat resistance of the polycarbonate material were reduced.
[0050] Examples 30-38 Different from Example 1, the preparation conditions and dosage of the antioxidant hydrolyzate are changed, as shown in Table 4.
[0051]
[0052] Comparative Example 4 The difference from Example 30 is that 18 parts of antioxidant hydrolysate are replaced by 18 parts of antioxidant 1010. That is, the antioxidant is not hydrolyzed but directly mixed with boron nitride grafted fluorine-containing silane to prepare the composite antioxidant.
[0053] Embodiment 39 The polycarbonate sun panels prepared in Examples 30-38 and Comparative Example 4 were subjected to weather resistance tests. Referring to the standard JG / T 116-2012 "Polycarbonate (PC) Hollow Panels", the color difference (≤5.0), yellow index change (≤3.0) and drop hammer impact (perforation characteristics) performance retention rate (≥60%) of the polycarbonate sun panels after 2000 hours of use were tested. The final test results are shown in Tables 5 and Figure 1 shown.
[0054]
[0055] like Figure 1 As shown in Table 5, the polycarbonate sunlight sheet prepared by the present invention has a color difference of 0.9-3.9, a yellow index change of 0.7-2.5, and a drop weight impact (perforation characteristic) performance retention rate of 80%-90%. Figure 1 It is shown that the weather resistance of Examples 30-34 changes by changing the type of antioxidant in the composite antioxidant. Among them, when Example 30 uses antioxidant 1010 as an antioxidant, the color difference and yellowness index change the least; the antioxidant forms 4 molecules of carboxylic acid antioxidant and 1 molecule of polyol after hydrolysis, and after the carboxylic acid antioxidant reacts with the fluorine-containing silane grafted with boron nitride, the phenolic hydroxyl groups therein exert good antioxidant and anti-yellowing effects; the anti-yellowing effect of Example 32 is second, but the drop hammer impact (perforation characteristics) performance retention rate is the highest; Examples 31 and 33 also contain phenolic hydroxyl structural units after hydrolysis, but the anti-yellowing effect is lower than that of Examples 30 and 30; the anti-yellowing effect of Example 34 is the worst, among which antioxidant 3114 is prepared into a composite antioxidant after hydrolysis, and its antioxidant effect is reduced after hydrolysis compared with the antioxidant composite of hindered phenol and hindered amine before hydrolysis. Table 5 shows that the results of Examples 30, 35, and 36 show that the antioxidants are hydrolyzed under appropriate pH conditions and used to prepare composite oxidants, and have good weather resistance. The results of Examples 30, 37, and 38 show that the color difference is the smallest, which is 0.9, when the amount of hydrolyzate used in Example 37 is 21 parts; the results of the yellow index change in Examples 30 and 37 are similar; Example 38 reduces the amount of hydrolyzate used, and the weather resistance decreases. In Comparative Example 4, the antioxidant is directly mixed with boron nitride grafted fluorinated silane, and the obtained polycarbonate is easy to precipitate under long-term use conditions, so the color difference of the antioxidant effect and the change of the yellow index increase, but the drop hammer impact (perforation characteristics) performance retention rate is not significantly reduced compared with the examples.
[0056] Examples 40-43 The difference from Example 27 is that the amounts of acrylsilsesquiane used are 47 parts, 43.5 parts, 41.5 parts and 40 parts respectively.
[0057] Examples 44-46 The difference from Example 27 is that the amounts of the modified MBS resin used are 53 parts, 54 parts, and 56 parts, respectively.
[0058] Embodiment 47 The difference from Example 27 is that the antioxidant 1010+TH-412S is replaced by the antioxidant 245+TH-412S.
[0059] Embodiment 48 Different from Example 27, the ratio of antioxidant 1 to antioxidant 2 is 1:1.
[0060] Comparative Example 5 Different from Example 27, only polycarbonate resin is used as the raw material to prepare the polycarbonate sunlight board.
[0061] Embodiment 49 The polycarbonate sun panels prepared in Examples 27, 40-48 and Comparative Example 5 were subjected to mechanical property tests. The impact resistance of the sun panels was tested according to the JG / T 116-2012 "Polycarbonate (PC) Hollow Panel" standard; the tensile properties of the sun panels were tested according to the ISO 527-1-012 standard. The test results are shown in Table 6.
[0062]
[0063] The maximum penetration force of the polycarbonate sun sheet prepared by the examples and comparative examples of the present invention under the drop hammer impact is 642-752N, and the tensile strength is 67.3-88.4MPa. The results of Examples 27 and 40-43 show that with the increase of the amount of propenyl silsesquiane, the tensile strength gradually decreases, and the tensile strength also decreases with the decrease in the amount. In the addition range of 40-44 parts, the addition of propenyl silsesquiane helps to enhance the tensile strength of the polycarbonate sun sheet. Examples 44-46 change the amount of modified MBS resin, and the tensile strength gradually decreases, but the maximum penetration force of the drop hammer impact gradually increases. Example 47 replaces the type of antioxidant. Compared with other examples, the hydrolyzed antioxidant 245 has a diol containing an ether structure, and the flexibility is increased. In Example 48, the amount of antioxidant TH-412S was increased, and the obtained polycarbonate sun sheet had the highest tensile strength of 88.4 MPa. The composite antioxidant prepared by hydrolyzing the antioxidant TH-412S had the highest flexibility, and the maximum penetration force of the drop hammer impact was lower than that of other examples. In Comparative Example 5, no modified MBS resin and composite antioxidant were added, and the maximum penetration force and tensile strength of the drop hammer impact of the polycarbonate sun sheet were greatly reduced compared with the examples. Overall, the polycarbonate sun sheet prepared by the present invention has good mechanical properties.
[0064] Examples 50-62 Different from Example 27, the dosage of the components of the mixture and the melt extrusion process parameters of the polycarbonate solar panel are changed, as shown in Table 7.
[0065]
[0066] Embodiment 63 The polycarbonate sun panels prepared in Examples 50-62 and Comparative Examples 6 and 7 were subjected to performance tests of light transmittance and yellow index changes. The thickness of the polycarbonate sun panel prepared in the present invention is 4 mm, and its light transmittance should meet the requirement of ≥75%. The test method was carried out in accordance with the test standard method shown in Example 39, and the final test results are shown in Table 8.
[0067]
[0068] The polycarbonate sun panel prepared by the present invention has a light transmittance of 70%-92%, and a yellowing index change of 0.6-2.6. In Examples 50-53, as the amount of modified MBS resin increases, the light transmittance of the sun panel as a whole shows a decreasing trend, and the light transmittance is the highest when the amount is 52.5 parts; but the yellowing index does not change significantly, and its value is in the range of 1.4-1.6. The results of Examples 52, 54-56 show that as the amount of composite antioxidant increases, the light transmittance shows an increasing and decreasing trend, and the yellowing index changes the least when the amount of composite antioxidant in Example 56 is 12 parts. When the composite antioxidant is added in excess, as shown in Comparative Example 6, the light transmittance decreases, but the yellowing resistance is improved. The results of Examples 55, 57, and 58 show that when the temperature of the conveying zone of Example 55 is 190°C, the transmittance is relatively high, and the yellowing index changes little; but when the temperature of the conveying zone is too high, the melting rates of different raw materials are inconsistent. When the speed of the twin-screw extruder is kept constant, the melt mixing of different raw materials is inconsistent, and the extruded materials are not uniform, which eventually leads to a decrease in the overall performance of the material. As shown in Comparative Example 7, the transmittance decreases and the yellowing resistance is poor. The results of Examples 55, 59-62 show that with the increase of the average temperature of other zones, the transmittance shows a trend of first decreasing and then increasing. When the average temperature of other zones is set to 300°C in Example 61, the yellowing resistance is the best. In summary, the polycarbonate sunlight sheet prepared by the present invention has high transmittance and good yellowing resistance.
[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A polycarbonate sunlight sheet, characterized in that: The polycarbonate sunlight board comprises the following components: Polycarbonate resin, 0-58 parts of modified MBS resin and 0-20 parts of composite antioxidant; The modified MBS resin preparation method is as follows: adding methacrylic acid aqueous solution and potassium persulfate to molten MBS resin, adding dopamine aqueous solution and 1-2 parts of 1,3-dicyclohexylcarbodiimide after reaction, stirring and reacting for 3 hours to obtain a dopamine grafted modified MBS resin precursor; the amount of dopamine in the dopamine aqueous solution is 8-12 parts; continuing to add 0-23.5 parts of phenyl phosphate, stirring and reacting for 10 hours, adding the 1,3-dicyclohexylcarbodiimide and 0-47 parts of acrylsilsesquiane, and reacting to obtain the modified MBS resin; The composite antioxidant preparation method is as follows: the boron nitride dispersion is heated to 60°C, and a fluorine-containing silane solution is added dropwise thereto under stirring to obtain a reaction solution; the ratio of boron nitride to fluorine-containing silane in the reaction solution is 1:0-0.4; Deionized water is added to the reaction solution, and the mixture is reacted for 5 hours, followed by washing and drying to obtain boron nitride grafted fluorinated silane; The pH value of the antioxidant solution is adjusted to 8.0-9.5 using potassium hydroxide solution, and the solution is refluxed at 60°C for 10 hours to obtain an antioxidant hydrolyzate; the antioxidant comprises an antioxidant 1 and an antioxidant 2 in a ratio of 1-4:1; 27-30 parts of the boron nitride grafted fluorine-containing silane and 16-21 parts of the antioxidant hydrolyzate are mixed to obtain a mixture; a mixed solution of ethanol and toluene and concentrated sulfuric acid are added to the mixture, the mixture is stirred and ultrasonicated, the reaction is refluxed at 110°C for 9 hours, the temperature is lowered, the mixture is layered, and the composite antioxidant is obtained by washing and drying.
2. A polycarbonate sunlight sheet according to claim 1, characterized in that: The modified MBS resin is 52-58 parts; the composite antioxidant is 8-20 parts.
3. The polycarbonate solar panel according to claim 1, characterized in that: The phenyl phosphate is one of diphenyl phosphate and phenyl phosphate benzenesulfonic acid.
4. The polycarbonate solar panel according to claim 1, characterized in that: The amount of phenyl phosphate used is 18-23.5 parts.
5. The polycarbonate solar panel according to claim 1, characterized in that: The amount of the acrylsilsesquiane is 40-47 parts.
6. The polycarbonate solar panel according to claim 1, characterized in that: The fluorine-containing silane is one of nonafluorotriethoxysilane, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, heptadecafluorooctyltriethoxysilane, heptadecafluorooctyltripropoxysilane, pentafluorooctyltripropoxysilane and heptadecafluorooctyltripropoxysilane.
7. The polycarbonate solar panel according to claim 1, characterized in that: The ratio of the boron nitride to the fluorine-containing silane is 1:0.3-0.
4.
8. The polycarbonate sunlight sheet according to claim 1, characterized in that: The oxidant 1 is one of antioxidant 1010 , antioxidant 1035 , antioxidant 245 , antioxidant 259 and antioxidant 3114 .
9. The polycarbonate solar panel according to claim 1, characterized in that: The second antioxidant is antioxidant TH-412S.
10. A method for preparing a polycarbonate sunlight sheet, characterized in that: The polycarbonate sun panel is prepared by mixing polycarbonate resin, modified MBS resin and composite antioxidant, and then putting them into a twin-screw extruder, controlling the temperature of the conveying zone to be 180-230° C., and the temperature of other zones to be 250-310° C., and then melt-extruding, drying and sheeting. The polycarbonate sun panel comprises the polycarbonate resin, the modified MBS resin and the composite antioxidant. The polycarbonate sun panel has an oxygen index of 29.3-41.9 and a flame retardant grade of V-0, V-1 and V-2. The hydrophobic angle of the board is 97.7°-146.1°, and the Vicat softening temperature is 70.9-116.2℃; the color difference of the polycarbonate sun panel is 0.9-3.9, the yellow index changes from 0.7-2.5, and the drop hammer impact (perforation characteristics) performance retention rate is 80%-90%; the maximum penetration force of the polycarbonate sun panel under drop hammer impact is 642-752N, and the tensile strength is 67.3-88.4MPa; the light transmittance of the polycarbonate sun panel is 70%-92%, and the yellowing index changes from 0.6-2.6.
Citation Information
Patent Citations
Polycarbonate copolymers and their manufacturing methods
CN102276821A
Transparent nonyellowing polycarbonate composition and preparation method
CN102719074B
An aging-resistant PC sun panel and its preparation method
CN111873585B
Modified polycarbonate and preparation method thereof
CN102382439A
Weather-resistant high-toughness polycarbonate composite material and preparation method thereof
CN114031923A